CLUSTERING ZONASI DAERAH RAWAN BENCANA ALAM DI PROVINSI SUMATERA BARAT MENGGUNAKAN ALGORITMA K-MEANS DAN LIBRARY GEOPANDAS - Wicaksono, David Aryo; Susetyo, Yeremia Alfa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Indonesia is one of the countries that are often affected by natural disasters because it is located on the Asia Pacific Ring of Fire. West Sumatra province is one of the most frequently hit by natural disasters including earthquakes. According to the Central Bureau of Statistics of West Sumatra from 2018-2021, there were 1,148 earthquake cases and 1,503 flood cases. The objective of this study is to reveal areas prone to natural disasters in West Sumatra province using K-Means algorithm and GeoPandas visualization. After doing data processing for the optimal K value, 3 clusters were obtained, namely, cluster 1 is not prone to natural disasters, cluster 2 is prone to natural disasters and cluster 3 is very prone to natural disasters. From this research, it is found that cluster 1 has 7 members of the region, cluster 2 has 11 members of the region, and cluster 3 has 1 member of the region.